Impact of Leaders’ Negative Behavior on Employee Silence with the Mediating role of Psychological Safety: A Study on Teachers of Higher Education Institutes of Pakistan - Noreen Ajmal; Dr. Safia Bano; Dr. Saubia Ramzan (Al-Qanṭara, 2024)
Leaders’ negative behavior is a dysfunctional leadership behavior that impacts its targets badly as well as the whole organization. On the basis of the conservation of resources (COR) theory, the present study adds knowledge on the impact of leaders’ adverse behavior. Mainly, a mediation model has been proposed wherein negative leadership predicts employees' silent behavior through psychological safety, with the leader. Data was collected through self-administered questionnaire from 643 teachers working in the thirty-one private sector universities of Pakistan through proportionate and convenience sampling approach. Results show a positive relationship between leaders’ negative behavior (Machiavellianism, Narcissism, Authoritative and Abusive) and Employee Silence. Further Psychological safety significantly mediates relationship between leaders’ negative behavior and employee silence. When psychological safety is reduced due to negative behavior, it contributes in increasing employee silence. The findings imply that negative behavior of leaders is prevailing in higher education institutes that requires immediate attention stressing the need of psychological trainings in higher education institutes of Pakistan.